Strain sharing and mobile genetic elements shape the interconnected resistomes of Campylobacter coli in Brazil - Ana Beatriz Garcez Buiatte; Leticia Roberta Martins Costa; Stephanie S. R. Souza; Nicole I. Zac Soligno; Roberta Torres de Melo; Paulo Marcel Armendaris; Daise Aparecida Rossi; Cheryl P. Andam (BMC Biology)
Abstract Background Campylobacter coli is a ubiquitous commensal in the gut of birds and mammals. It causes acute gastroenteritis in humans when contaminated livestock meat is consumed and can be fatal in vulnerable individuals. Here, we aim to characterize the population genomic structure and antimicrobial resistance (AMR) dissemination of C. coli in Brazil contextualized against a South American background. Results We analyzed 32 newly sequenced short-read genomes from Brazil and 158 previously sequenced genomes from different locations in South America. Clonal complex CC828, which is known to be predominant in agriculture and human diseases, accounted for 82.4% of the Brazilian genomes (n = 108). We identified six mutations, 15 acquired genes, and one operon (cmeABC) that were associated with AMR in the Brazilian population. Six AMR determinants (aad9, aph(3')-IIIa, gyrA T86I, 23S A2075G, blaOXA-460, tet(O)) displayed co-occurrence albeit at different paired combinations and probabilities. The Brazilian genomes showed close phylogenetic relationship with those from Chile, Ecuador, and Peru. Across the four countries, AMR determinants associated with putative plasmids or transposable elements included those related to aminoglycosides, streptothricin, tetracyclines, and multidrug resistance. Conclusions The widespread dissemination of CC828 and their mobile genetic elements shape AMR distribution in C. coli across Brazil. A long-term epidemiological and genomic surveillance system in the country will be useful to determine how campylobacteriosis can be controlled effectively and the scale at which interventions need to be enforced.